Structural studies on the reaction of isopenicillin N synthase with a sterically demanding depsipeptide substrate analogue. - Ge, W; Clifton, I; Howard-Jones, A; Stok, J; Adlington, R; Baldwin, J; Rutledge, P (2009)
Isopenicillin N synthase (IPNS) is a nonheme iron(II)-dependent oxidase that catalyses the central step in penicillin biosynthesis, conversion of the tripeptide delta-L-alpha-aminoadipoyl-L-cysteinyl-D-valine (ACV) to isopenicillin N (IPN). This report describes mechanistic studies using the analogue delta-(L-alpha-aminoadipoyl)-(3S-methyl)-L-cysteine D-alpha-hydroxyisovaleryl ester (A(S)mCOV), designed to intercept the catalytic cycle at an early stage. A(S)mCOV incorporates two modifications from the natural substrate: the second and third residues are joined by an ester, so this analogue lacks the key amide of ACV and cannot form a beta-lactam; and the cysteinyl residue is substituted at its beta-carbon, bearing a (3S)-methyl group. It was anticipated that this methyl group will impinge directly on the site in which the co-substrate dioxygen binds. The novel depsipeptide A(S)mCOV was prepared in 13 steps and crystallised with IPNS anaerobically. The 1.65 A structure of the IPNS-Fe(II)-A(S)mCOV complex reveals that the additional beta-methyl group is not oriented directly into the oxygen binding site, but does increase steric demand in the active site and increases disorder in the position of the isovaleryl side chain. Crystals of IPNS-Fe(II)-A(S)mCOV were incubated with high-pressure oxygen gas, driving substrate turnover to a single product, an ene-thiol/C-hydroxylated depsipeptide. A mechanism is proposed for the reaction of A(S)mCOV with IPNS, linking this result to previous crystallographic studies with related depsipeptides and solution-phase experiments with cysteine-methylated tripeptides. This result demonstrates that a (3S)-methyl group at the substrate cysteinyl beta-carbon is not in itself a block to IPNS activity as previously proposed, and sheds further light on the steric complexities of IPNS catalysis.